Porovnání vlastností hlasu klasických a popových zpěvaček - Marek Frič; Iva Podzimková; Jana Jelínková (Musicologica Brunensia, 2021)
The aim of this work is to compare perceptual, acoustic and electroglottographic features of voice within six opera female singers and five pop female singers. The analysis was done for vowels A, I and U and was performed on 0.5 s long samples of scales singing ranging from C4 to C6 in 4 dynamic levels and samples taken from 4 chosen tones within an octave sung with gradually increased intensity. Evaluation by listening proved a fundamental difference between the perception of darkened colour of the voice with pronounced vibrato typical for opera singers and light, bright and narrow sound without vibrato typical for pop singers. The style of voice modulation, especially the range of pitch modulation (the difference came up to 2 semitones in the highest notes), essentially differentiated individual styles of opera singers. Pop singers had a higher rate of periodical irregularities and also a higher frequency of pitch modulation. Opera singers generally reached higher maximum SPL levels in C5-C6 octave. Pop singers had higher maximum SPL levels only in the middle of C4-C5 octave for vowel A. Electroglottography demonstrated different phonation settings within singing genres. The most significant difference concerned medium and loud dynamic level in the range of one and a half octave, where the voice of pop singers showed higher values of contact quotient of vocal folds. Moreover, the systematic difference was proved in changes of the shape of EGG pulses (from wavegrams) with increasing pitch. Pop singers gradually reduced amplitude in vocal folds decontact area, while opera singers gradually increased relative amplitude of EGG pulses in the same area. Spectral analysis proved fundamental differences especially in lower in lower parts of the vocal range. Opera singers enriched the sound particularly between 2 and 5 kHz by bringing positions of third to fifth formants slightly together. Pop singers had significantly higher energy values in higher parts of vocal range. Acoustic properties have shown that acoustic energy of the pop singers reached higher frequency bands above 5 kHz. Global spectral features acoustically differentiated the best opera and pop singing styles, in particular features, which are independent on positions of vowel formants. The darkened timbre of opera voice can be explained by a generally lower larynx position, which also means that the first harmonic is strengthened. Together with thinner vocal folds (less vocal folds contact), the perception of a head voice is stronger. Also, an inertial effect of the vocal tract, which strengthens the oscillations of the entire vocal system, works better. In the C5-C6 octave, opera singers can change register to full head. Those two practices make it possible: preservation of the M2 mechanism even on the highest notes and tuning the first formant up to the first harmonic. On the other hand, the voice of pop singers is closer to the neutral speaking voice setting of the vocal tract. That means higher larynx position, thicker vocal folds (more vocal folds contact) and often even some noise element.